IMPLEMENTASI SISTEM PENDUKUNG KEPUTUSAN DENGAN METODE AHP UNTUK PENENTUAN PRIORITAS PENGADAAN BARANG DI GUDANG - Wibowo, Sadiq Ardo; Hernando, Luki; Rahman, Taufiq; Firdasari, Firdasari; Shodiq, Muhammad Fajar (Universitas Putera Batam, 2024)
This study designs a decision support system using the Analytical Hierarchy Process (AHP) method to determine the priority of procurement of goods in the Sabila Craft Batam warehouse. This system is designed to help management determine the order of procurement priorities based on the criteria of inventory levels, demand, lead time, costs, and the importance of goods for operations. Through a hierarchical structure, the AHP method breaks down complex problems into objectives, criteria, and alternatives, and performs pairwise comparisons between criteria to obtain the priority weight of each element. The calculation results show that the Wall Clock product has the highest priority with a weight value of 0.302, followed by Keychains (0.299), Tumblers (0.274), House Numbers (0.262), and Baby Biodata (0.146). All consistencies meet a ratio below 0.1, indicating that the evaluations carried out are consistent. The resulting system allows for more objective and structured decision making, so that it can optimize warehouse efficiency, reduce the risk of excess or shortage of inventory, and speed up the procurement process.